CO2 Capture and in situ Catalytic Transformation - Fu, Hong-Chen; You, Fei; Li, Hong-Ru; He, Liang-Nian (Frontiers in Chemistry, 2019)
The escalating rate of fossil fuel combustion contributes to excessive CO2 emission and the resulting global climate change has drawn considerable attention. Therefore tremendous efforts have been devoted to mitigate the CO2 accumulation in the atmosphere. Carbon capture and storage (CCS) strategy has been regarded as one of the promising options for controlling CO2 build-up. However, desorption and compression of CO2 need extra energy input. To circumvent this energy issue, carbon capture and utilization (CCU) strategy has been proposed whereby CO2 can be captured and in situ activated simultaneously to participate in the subsequent conversion under mild conditions, offering valuable compounds. As an alternative to CCS, the CCU has attracted much concern. Although various absorbents have been developed for the CCU strategy, the direct, in situ chemical conversion of the captured CO2 into valuable chemicals remains in its infancies compared with the gasous CO2 conversion. This review summarizes the recent progress on CO2 capture and in situ catalytic transformation. The contents are introduced according to the absorbent types, in which different reaction type is involved and the transformation mechanism of the captured CO2 and the role of the absorbent in the conversion are especially elucidated. We hope this review can shed light on the transformation of the captured CO2 and arouse broad concern on the CCU strategy.